Original paperInfluence of combined botanical extract preparation on body composition – results from double blind randomized clinical trial - Pilaczyńska-Szcześniak, Łucja; Rzymski, Paweł; Pischel, Ivo (Archives of Medical Science, 2006)
Introduction: Obesity is becoming a great cause of concern in many countries. To shift the energy balance towards expenditure, dietary supplements should be designed to increase thermogenesis, lipolysis, loss of body water, and activation of digestive enzymes. Material and methods: Double blind randomized placebo-controlled clinical trial to evaluate a botanical water extract composed of green tea extract, bean peel and asparagus. During 56 days of the study body composition, anthropometric measurements and biochemical parameters were estimated in fifty-one healthy, moderately obese subjects. Results: Forty-two subjects completed the study according to the protocol. In the active preparation group, weight, BMI, percent of body fat, waist, hip and waist-to-hip ratio were not statistically different compared to placebo. The sum of skinfolds differed significantly. When selecting a subgroup of patients with hypercholesterolaemia (n=21), in the active extract group the change in body composition index (BCI) and fat mass (FM) were significant (p=0.037 and p=0.019 respectively) in patients with hypercholesterolaemia when compared to normocholesterolaemic patients. Fat-free mass (FFM) did not change significantly in the active extract group (p=0.083) when hypercholesterolaemic and normocholesterolaemic patients were compared. None of the parallel parameters (FM and FFM change, BCI) changed significantly in the placebo group when compared to hypercholesterolaemic and normocholesterolaemic subjects. Conclusions: There was no statistically significant change in weight, BMI or percent of body fat measured by bioimpedance in the active extract and placebo groups. Obese patients with hypercholesterolaemia benefited from the active extract, with reduced total fat mass and a positive influence on the body composition improvement index.